Bahasa Kethoprak Wahyu Manggolo: Kajian sosiolinguistik - Kriswanto, Yoga; Prembayun Miji Lestari (Universitas Negeri Malang, 2025)
The language of Kethoprak Wahyu Manggolo: A sociolinguistic study Kethoprak is a form of traditional Javanese theater that serves not only as entertainment but also as a medium of communication and cultural preservation. This study is motivated by the limited number of works that examine linguistic aspects in kethoprak performances, particularly from a sociolinguistic perspective. It aims to investigate language variation in performances by Kethoprak Wahyu Manggolo through a sociolinguistic approach. The analysis focuses on varieties of Javanese, such as ngoko, krama madya, and krama alus, and on how their use reflects cultural values and social relations within Javanese society. The research employs a qualitative descriptive method, using non-participatory observation of dialogue in performance videos. The findings indicate that language variation is guided not only by linguistic norms, but also functions as a symbol of social status, a vehicle for emotional expression, and a means of conveying moral values and subtle social critique. The speech styles used by characters in the performances mirror a hierarchical social structure, power relations, and the cultural identity of Javanese society. This study underscores the importance of traditional performing arts as a medium for preserving language and local cultural values. Kethoprak merupakan salah satu bentuk teater tradisional Jawa yang tidak hanya berfungsi sebagai hiburan, tetapi juga sebagai media komunikasi dan pelestarian budaya. Penelitian ini dilatarbelakangi oleh belum banyaknya kajian yang menelaah aspek kebahasaan dalam pementasan kethoprak, khususnya dari sudut pandang sosiolinguistik. Penelitian ini bertujuan untuk mengkaji variasi bahasa dalam pementasan Kethoprak Wahyu Manggolo dengan pendekatan sosiolinguistik. Fokus kajian diarahkan pada bentuk-bentuk ragam bahasa Jawa seperti ngoko, krama madya, dan krama alus, serta bagaimana penggunaan bahasa tersebut mencerminkan nilai budaya dan relasi sosial masyarakat Jawa. Metode penelitian yang digunakan adalah deskriptif kualitatif dengan teknik observasi non-partisipatif terhadap dialog dalam video pementasan. Hasil penelitian menunjukkan bahwa penggunaan variasi bahasa tidak hanya mengikuti norma linguistik, tetapi juga berfungsi sebagai simbol status sosial, alat ekspresi emosi, dan sarana penyampaian nilai moral serta kritik sosial secara halus. Ragam bahasa yang digunakan tokoh-tokoh dalam pementasan mencerminkan struktur sosial yang hierarkis, relasi kekuasaan, dan identitas kultural masyarakat Jawa. Penelitian ini menegaskan pentingnya seni pertunjukan tradisional sebagai media pelestarian bahasa dan nilai budaya lokal.